2004
DOI: 10.1592/phco.24.16.1578.50945
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous Ethanol for the Treatment of Alcohol Withdrawal Syndrome in Critically Ill Patients

Abstract: Critically ill patients with alcoholism are at greater risk of morbidity and mortality from alcohol withdrawal syndrome than are patients without alcoholism. Benzodiazepines are considered the drugs of choice for the prevention and treatment of alcohol withdrawal syndrome, but some studies have suggested that intravenous ethanol may be as effective as those agents, as well as being less sedating. We evaluated the evidence regarding the use of intravenous ethanol for the prevention and treatment of alcohol with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 26 publications
0
19
0
2
Order By: Relevance
“…Intravenous alcohol may be a useful treatment for preventing AWS, but only if done within a strict protocol 74 75. However, there is little evidence from controlled studies to support this practice over standard treatments, and there are concerns regarding the efficacy, pharmacokinetic profile and narrow therapeutic index of ethanol, particularly in critically ill patients 76. Tiapride, a benzamide with D2 and D3 antagonist activity, reduces hyperhidrosis, agitation and tremor during alcohol withdrawal, and may be a useful adjunct to other agents used in the treatment of AWS 77 78…”
Section: Managementmentioning
confidence: 99%
“…Intravenous alcohol may be a useful treatment for preventing AWS, but only if done within a strict protocol 74 75. However, there is little evidence from controlled studies to support this practice over standard treatments, and there are concerns regarding the efficacy, pharmacokinetic profile and narrow therapeutic index of ethanol, particularly in critically ill patients 76. Tiapride, a benzamide with D2 and D3 antagonist activity, reduces hyperhidrosis, agitation and tremor during alcohol withdrawal, and may be a useful adjunct to other agents used in the treatment of AWS 77 78…”
Section: Managementmentioning
confidence: 99%
“…For example, alcohol administration by intravenous route is known to affect the erythrocytes when present in high concentrations [128] . Thus alcohol administration by intravenous route is currently limited to creating an acute alcohol exposure during treatment of alcohol withdrawal symptoms [151] , while administration by intraperitoneal injections is widely preferred in research settings.…”
Section: Non-human Aaa Modelsmentioning
confidence: 99%
“…However, among those who have reported the use of ethanol in acute care settings, results and recommendations have been both negative (36), and positive(37). Most recently studies have reported alcohol as a therapeutic intervention to be safe and effective in isolated acute care settings (37).…”
Section: Discussionmentioning
confidence: 99%